Perlindungan Hukum Terhadap Konsumen dari Pelaku Usaha Periklanan Menurut UU Nomor 8 Tahun 1999 - Fitriah, Fitriah (Solusi, 2019)
The general provisions of Article 1 paragraph 6 of Act Number 8 of 1999 concerning Consumer Protection, that "Promotion is an activity to introduce or disseminate information on an item and / or service to attract consumers' buying interest in goods and / or services that will be and are being traded". Advertising is a form of information, a tool for product business actors to introduce their products to the public in order to attract people to use these products. the public will get an idea of a product if the product is advertised, but the problem is that the ad does not always provide true or complete information about a product, so many consumers feel cheated by outstanding advertisements. There are several articles regulating advertisements on legal protection against consumers, namely Article 9, Article 10, Article 12, Article 13, Article 17, and Article 20. If a business actor has made an agreement with the consumer then the businessman deceives with the purpose of fraud then it can be used as an excuse to cancel the agreement stipulated in Article 1321 of the Civil Code and article 1328 of the Civil Code. However, if there is no contractual or contractual relationship between the business actor and the consumer, the consumer is harmed as a result of the advertisement lie, for example a consumer is injured and loses, the business actor is declared as a party that is violated by Article 1365 of the Civil Code.